Chinese Economic and Technical Assistance to Africa in the New Century - Liu, Jun (International Journal of Social Sciences and Public Administration, 2024)
In the 21st century, China has strengthened its economic and technical assistance to Africa. The amount of assistance has increased significantly, the subjects of assistance have become more diversified, and the methods of assistance have become more diverse. In particular, China has focused on the training of local talents and human resources development in African countries, thus promoting the rapid economic and social development of Africa. The reason for this is not only the needs of China’s economic and social development, but also the strong promotion of the international community. It is also because China’s foreign aid has gradually been aligned with international standards and its internationalization has gradually increased. Through economic and technical assistance to Africa, China and Africa have achieved mutual benefit and win-win results.